Academic Procrastination in Completing Students’ Thesis - Marif, Abdul; Konadi, Husrin (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2023)
A thesis is a final project that must be completed by final-year students to complete their education in college. There are many problems experienced by students when completing their thesis, including the behavior of academic procrastination. Academic procrastination is a delaying behavior to complete academic tasks. This study aims to describe the academic procrastination of students. This study uses a qualitative method with a descriptive approach. The participants in this study were final-year students who had passed 1 year of thesis completion, namely 4 people. The results showed that 4 participants in this study carried out academic procrastination in completing their thesis. This can be seen from the results of interviews and observations made by researchers. Various factors that influence students’ procrastination behavior include not being able to delay pleasure, lack of motivation from parents, distrust of self-ability, and participating in peer relationships.